Library dementia services : how to meet the needs of the Alzheimer's community - Dickey, Timothy J. (Emerald Publishing Limited, 2020)
There are 50 million people globally living with Alzheimer's disease and related dementias, and tens of millions further who are their caregivers. As a public service, it is important that library and information professionals learn to serve and assist those with dementia. Designed for seasoned professionals and library science students alike, this book first presents a complete overview of the spectrum disease known as Alzheimer's dementia, as well as a basic understanding of the information needs of dementia caregivers. It then explores best practices, guidelines, and concrete ideas for serving those with dementia and their caregivers, including: Customer service and communication, with evidence-based suggestions for working with this population; Information resources to best meet the reference needs of the community, as grounded in LIS user studies and health informatics; Collection development for ongoing and appropriate mental and social stimulation of those experiencing cognitive decline; and Programming ideas for both communities, with a wide variety of focus and content. Lifelong learning, mental stimulation, and social connections are central to libraries' core mission. Readers, both from library and information science and in related social services and social sciences disciplines, will gain a comprehensive toolkit for service both to those in cognitive decline and their caregivers, meeting the needs of both communities with thoughtful and innovative practices.
Includes index.
Keywords: Libraries and people with mental disabilities.; Dementia -- Patients -- Books and reading.; Language Arts & Disciplines -- Library & Information Science -- General.; Community & outreach services.; elektronické knihy; electronic books